Comparative effectiveness of different localization techniques for non-palpable breast cancer. A systematic review and network meta-analysis. Issue 1 (January 2022) - Athanasiou, Christos; Mallidis, Evangelos; Tuffaha, Hussein
Abstract: Background: Several localization techniques are in use for localization of non palpable breast cancer but data on comparative effectiveness of these techniques are sparse. Our aim was to provide the first comparative effectiveness data on the topic. Methods: PubMed, Ovid, Scopus and Cochrane library were searched for randomized controlled trials. Pairwise meta-analysis was performed when more than 2 studies reported on the same head-to-head comparison. Network meta-analysis was performed in Stata. Results: Eighteen studies with 3112 patients were identified. A star shaped network was formed for every outcome as all studies had as common comparator the wire localization technique (WGL). Ultrasound guided surgery (UGS) had decreased positive margin both in the pairwise [OR = 0.19(0.11, 0.35); P < 0.01] and network meta-analysis OR = 0.19 (0.11, 0.60). There was also a statistically significant reduction in re-operation rate [OR = 0.19 (0.11, 0.36); P < 0.01] and operative time [MD = −4.24(-7.85, -0.63); P = 0.02] as compared to WGL in pairwise meta-analysis. Re-operation rate and operative time did not hold there statistical significance in network meta-analysis. On network meta-analysis UGS had a statistically significant reduction in positive margin as compared to radio-guided occult lesion localization (ROLL) OR = 0.19 (0.11, 0.6) and radioactive seed localization (RSL) OR = 0.26(0.13, 0.52). UGS had a 54.6% of being the best technique for positive margin. All techniques were equivalent for successful excision, localization complications, operative time and overall complications. Conclusions: UGS has potential benefits in reduction of positive surgical margin, the rest of the techniques seem to have equivalent efficacy. Further randomized trials are required to verify these results.